The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10571-009-9399-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Endothelin-1 and its Receptors in the Spiral Ganglion Neurons of Mouse

Abstract: Endothelin-1 (ET-1) is a peptide with various biological functions, such as vasoconstriction and cell proliferation. ET-1 was reported to be widely distributed throughout the animal body, including nervous system. The expression and localization of ET-1 and its receptors [endothelin type-A receptor (ETAR) and endothelin type-B receptor (ETBR)] in the spiral ganglion neurons have not been reported before. In this study, their presence in the mouse spiral ganglion neurons was detected at mRNA and protein levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Nuclear localization of endothelin receptors has been demonstrated in rat liver [56], rat cardiomyocytes [12], and mouse spiral ganglion neurons [57]. We previously reported that ETB immunoreactivity was primarily associated with nuclear membranes in ventricular myocytes whereas ETA was associated with the cell surface and T-tubular network as well as showing a weaker association with nuclear or perinuclear membranes [12,13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nuclear localization of endothelin receptors has been demonstrated in rat liver [56], rat cardiomyocytes [12], and mouse spiral ganglion neurons [57]. We previously reported that ETB immunoreactivity was primarily associated with nuclear membranes in ventricular myocytes whereas ETA was associated with the cell surface and T-tubular network as well as showing a weaker association with nuclear or perinuclear membranes [12,13].…”
Section: Discussionmentioning
confidence: 96%
“…Chimeric ETA and ETB constructs reveal the cytoplasmic C-terminal domain of ETA is sufficient to specify receptor recycling whereas the comparable domain in ETB specifies delivery to lysosomes [4,6]. In ventricular myocytes [12] and mouse spiral ganglion neurons [57], which express both ETA and ETB, ETB is primarily associated with the nuclear membranes whereas ETA is at the cell surface. Hence, it is unlikely that the presence of ETB on nuclear membranes is a result of 'overflow' from the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution provides a fair idea of how endothelin‐1 functions in the inner ear. It is advocated that endothelin‐1 plays a role in regulating the function of the inner ear as a peptide with mitogenic, antiapoptotic, and neural‐transmission effects …”
Section: Introductionmentioning
confidence: 99%
“…It is advocated that endothelin-1 plays a role in regulating the function of the inner ear as a peptide with mitogenic, antiapoptotic, and neural-transmission effects. 7 The human endothelin-1 (EDN1) gene is located on chromosome 6p and consists of five short exons and four introns. Various single nucleotide polymorphisms (SNPs) have been identified in the EDN1 gene and have been reported to be associated with the susceptibility and prognosis of various diseases, including hypertension, glaucoma, heart failure, diabetic retinopathy, and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…10,38 ET B immunoreactivity has also been detected on mouse cochlear spiral ganglion nuclei, whereas ET A immunoreactivity was primarily cytosolic in these cells. 39 Subsequent experiments showed that the ET B -selective antagonist BQ788 prevented both rhodamine-ET-1 and rhodamine-endothelin-3 (ET-3) from binding to nuclear sites in both isolated cardiac nuclei and Triton X-100-skinned adult cardiomyocyte preparations. 40 Hence, in cardiomyocytes, ET A is the major endothelin receptor at the cell surface, 41,42 whereas the nuclear ETR is ET B .…”
mentioning
confidence: 99%